2022
DOI: 10.52965/001c.33754
|View full text |Cite
|
Sign up to set email alerts
|

The eradication rate of infection in septic knee arthritis according to the Gächter Classification: a systematic review

Abstract: Introduction Knee septic arthritis rapidly damages the knee joint. Gächter described a classification of joint infections based on arthroscopic findings: an arthroscopic staging of the common disease has prognostic and therapeutic consequences. The aim of this systematic review was to analyze the application of the Gächter classification system to knee septic arthritis, evaluating prognostic and therapeutic implications of this classification. Materials and Methods A comprehensive electronic search of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Therefore, the overall conclusion of this review is that neither arthroscopy nor arthrotomy showed superiority in reducing reoperation rate. This aligns with findings of previous reviews of this subject [ 11 , 28 , 38 ] with the exception of Acosta‐Olivo et al [ 2 ] who found that arthroscopic washout was superior.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the overall conclusion of this review is that neither arthroscopy nor arthrotomy showed superiority in reducing reoperation rate. This aligns with findings of previous reviews of this subject [ 11 , 28 , 38 ] with the exception of Acosta‐Olivo et al [ 2 ] who found that arthroscopic washout was superior.…”
Section: Discussionsupporting
confidence: 91%
“…In total, 17,140 index procedures for septic arthritis were identified. We note previous systematic reviews on this topic [ 2 , 11 , 28 , 38 ]; however, ours is the first to include Upfill‐Brown et al's [ 45 ] 14,365 subjects. In light of limited RCT on this subject, we believe ours to be the most definitive body of evidence to date for comparing arthroscopy to arthrotomy for septic knee arthritis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Its major complication is dislocation due to its intrinsic instability; in our case reports, there was a persistent fracture of the acetabulum, which did not allow the implanting of a hip spacer without significant risk [ 30 , 31 ]. Thus, we treated the fracture-related infection with a two-stage revision, while septic arthritis of the hip with a one-stage revision [ 14 , 32 ]. In the second stage, we planned to perform the definitive osteosynthesis and implant of the total hip arthroplasty after the second aggressive debridement with irrigation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%